(untitled) (Teaching and Learning Inquiry, 2021)
In this article, we share themes and tensions experienced by humanities faculty undertaking a scholarship of teaching & learning (SoTL) project as part of a multi-campus, grant-funded initiative. Faculty participants in the project iteratively transformed a course to improve one or more aspects of their students’ learning over a three-year period and documented the process and results in a course portfolio. To support their individual and collaborative work, each of the four campuses had a local leader, and participants met regularly with campus teams, convening with the full group annually for cross-campus knowledge exchange and peer review. At the project conclusion campus leaders gathered participant reflections and discovered a pattern of tensions that included: disciplinary ways of knowing, ways to represent knowing, and ways of writing and sharing. These tensions are similar to those identified elsewhere and can be potential impediments to this work for some in the humanities. Explicitly addressing those potential tensions while helping faculty see how their own disciplinary approaches can help them investigate their course practices is a useful first step toward more contributions from humanities scholars.